Spectral and computational features of the binding between riparins and human serum albumin - Camargo, Cintia Ramos [UNESP]; Caruso, Ícaro Putinhon [UNESP]; Gutierrez, Stanley Juan Chavez; Fossey, Marcelo Andres [UNESP]; Filho, José Maria Barbosa; Cornélio, Marinônio Lopes [UNESP] (Elsevier, 2018)
The green Brazilian bay leaf, a spice much prized in local cuisine (Aniba riparia, Lauraceae), contains chemical compounds presenting benzoyl-derivatives named riparins, which have anti-inflammatory, antimicrobial and anxiolytic properties. However, it is unclear what kind of interaction riparins perform with any molecular target. As a profitable target, human serum albumin (HSA) is one of the principal extracellular proteins, with an exceptional capacity to interact with several molecules, and it also plays a crucial role in the transport, distribution, and metabolism of a wide variety of endogenous and exogenous ligands. To outline the HSA–riparin interaction mechanism, spectroscopy and computational methods were synergistically applied. An evaluation through fluorescence spectroscopy showed that the emission, attributed to Trp 214, at 346 nm decreased with titrations of riparins. A static quenching mechanism was observed in the binding of riparins to HSA. Fluorescence experiments performed at 298, 308 and 318 K made it possible to conduct thermodynamic analysis indicating a spontaneous reaction in the complex formation (ΔG < 0). The enthalpy-entropy balance experiment with a molecular modeling calculation revealed that hydrophobic, hydrogen bond and non-specific interactions are present for riparin I–III with HSA. The set of results from fractional fluorescence changes obtained through Schatchard was inconclusive in establishing what kind of cooperativity is present in the interaction. To shed light upon the HSA-riparins complex, Hill's approach was utilized to distinguish the index of affinity and the binding constant. A correspondence between the molecular structures of riparins, due to the presence of the hydroxyl group in the B-ring, with thermodynamic parameters and index of affinity were observed. Riparin III performs an intramolecular hydrogen bond, which affects the Hill coefficient and the binding constant. Therefore, the presence of hydroxyl groups is capable of modulating the interaction between riparins and HSA. Site marker competitive experiments indicated Site I as being the most suitable, and the molecular modeling tools reinforced the experimental results detailing the participation of residues.
Keywords: Binding density function; Computational methods; Drug displacement; Fluorescence; Human serum albumin; Riparin